SHOULDER INJURY IN SURFING: A SYSTEMATIC REVIEW WITH META-ANALYSIS - Eduardo Bracco Cianciarulo; Tieslivi da Silva Vieira; Paulo Henrique Schmidt Lara; Paulo Santoro Belangero; Benno Ejnisman (Acta Ortopédica Brasileira, 2024)
ABSTRACT Objective: To establish the epidemiological profile of shoulder injuries suffered by surfers, through the injury proportion rate, type, mechanism and/or severity, caused by surfing. Methods: This systematic review was conducted and written in accordance with the guidelines for systematic reviews– PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). The bibliographic research was carried out between January 2020 and January 2022 in journals indexed in the Web of Science, SPORTDiscus, PubMed, Scopus, Cochrane and Embase databases. Data were analyzed in RStudio, and the methodological quality of the studies was assessed. Results: Ten studies were included, all of which were retrospective in cross-sectional design and had an average methodological quality of 75%. The meta-analysis showed an injury incidence rate of 14.88%. Odds ratio analysis showed that injuries of joint origin are 7.26 times significantly higher in individuals with shoulder injuries, and injuries of bone origin and skin injuries had reduced odds of 70% and 89%, respectively. The most common mechanism of injury was the movement of paddling (57,68%), with the average prevalence of acute injuries being 31.53% and chronic injuries being 68.47%. Conclusion: There was a scarcity and/or variation in the categorization of data regarding injuries in the shoulder region resulting from surfing, with injuries of joint and musculotendinous origin being frequent; and rowing, the most overloading factor. Level of evidence II, Systematic Review.